2021
DOI: 10.1186/s10020-021-00364-6
|View full text |Cite
|
Sign up to set email alerts
|

MiR-100 overexpression attenuates high fat diet induced weight gain, liver steatosis, hypertriglyceridemia and development of metabolic syndrome in mice

Abstract: Background Diet-induced obesity can result in the development of a diverse spectrum of cardiovascular and metabolic diseases, including type 2 diabetes, dyslipidemia, non-alcoholic liver steatosis and atherosclerotic disease. MicroRNAs have been described to be important regulators of metabolism and disease development. Methods In the current study, we investigated the effects of ubiquitous miR-100 overexpression on weight gain and the metabolic ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 53 publications
(59 reference statements)
0
8
0
Order By: Relevance
“…The combination of n-3 long chain polyunsaturated fatty acids and flavan-3-ols prevented the high-fat high-fructose diet-induced MAFLD and liver FABP4 expression [ 131 ], suggesting an impact of FABP4 in the disease. Moreover, the reduction in the liver expression of FABP4 by the ubiquitous miR-100 overexpression was in line with the effect of this molecule protecting from high fat diet-induced liver steatosis [ 132 ]. The Huang-Qi San, a combination of three traditional Chinese medicines used for the treatment of several diseases, given its anti-oxidant, anti-diabetic, hepatoprotective, immunological and anti-inflammatory properties, reduced both plasma FABP4 levels and liver lipid accumulation in high fat diet-fed rats [ 133 ].…”
Section: Fabp4 As a Potential Therapeutic Target For Mafldmentioning
confidence: 87%
“…The combination of n-3 long chain polyunsaturated fatty acids and flavan-3-ols prevented the high-fat high-fructose diet-induced MAFLD and liver FABP4 expression [ 131 ], suggesting an impact of FABP4 in the disease. Moreover, the reduction in the liver expression of FABP4 by the ubiquitous miR-100 overexpression was in line with the effect of this molecule protecting from high fat diet-induced liver steatosis [ 132 ]. The Huang-Qi San, a combination of three traditional Chinese medicines used for the treatment of several diseases, given its anti-oxidant, anti-diabetic, hepatoprotective, immunological and anti-inflammatory properties, reduced both plasma FABP4 levels and liver lipid accumulation in high fat diet-fed rats [ 133 ].…”
Section: Fabp4 As a Potential Therapeutic Target For Mafldmentioning
confidence: 87%
“…Transgenic mice with miR-100 overexpression demonstrated reduced weight gain and increased glucose tolerance, insulin sensitivity, and energy expenditure compared to wild-type controls on a high-fat diet, despite similar calorie intake [81]. Moreover, serum and visceral adipose miR-100 levels were lower in obese normoglycemic and type 2 diabetic human individuals compared to lean and non-diabetics [40].…”
Section: Discussionmentioning
confidence: 95%
“…The overexpression of these two miRNAs was reported in the adipose tissue of obese individuals [ 26 , 54 , 55 ]. However, preclinical studies suggested their different roles in the development of obesity-associated complications: while the overexpression of miR-100 protects against liver steatosis, hypertriglyceridemia, and the development of metabolic syndrome in mice, the obesity-related increase in miR-143 levels predisposes them to insulin resistance [ 56 , 57 ]. In our study, we found negative correlations between the expressions of these two miRNAs and ESR1 mRNA levels in the SAT of the obese study participants.…”
Section: Discussionmentioning
confidence: 99%